PREJUDICE TOWARDS INDIAN IN MORAIS’ THE HUNDRED-FOOT JOURNEY NOVEL - Rohmah, Henny; Kuncara, Singgih Daru; Lubis, Indah Sari (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research analyzes prejudice in The Hundred Foot Journey Novel. The novel explains about prejudice which is done by French towards Indian. This research aims to reveal rejections generated from prejudice that happened to Indian and to describe the behaviors of Indian when they experienced prejudice. This research uses Gordon Allport’s prejudice theory and then the prejudice generated several rejections: antilocution, avoidance, discrimination, physical attack and extermination. Prejudice also generated behaviors from the victim of it, in this case behaviors became the response. The theory of behavior is also based on Gordon Allport which divided into extropunitive and intropunitive behavior. The method of this research is qualitative research with mimetic approach. The data are narrations and dialogues that related to prejudice and also rejections from prejudice. The data are analyzed by using Allport’s theory and then the process of data analysis is using Miles and Huberman’s theory. The result of this research is four out of five rejections from prejudice are found in this research. There were antilocution, avoidance, discrimination, and physical attack. Meanwhile in this research, extropunitive was the most dominant behavior as the response from the Indian.